(untitled) (Global Journals of Research in Engineering, 2011)
The use of cutting fluids in machining is indispensible. However, the microbial contamination of the fluids limits their usage. In the present work nano cutting fluids with carbon nano tube (CNT) inclusion are prepared for use in Minimum quantity lubrication (MQL). Microbial contaminations of these samples are analyzed along with the fluids under stored condition over a span of one month, and the bacteria present in the fluid is isolated and identified to help provide the appropriate remedial actions.